Advanced Organic Permeable‐Base Transistor with Superior Performance. (20th October 2015) - Klinger, Markus P.; Fischer, Axel; Kaschura, Felix; Scholz, Reinhard; Lüssem, Björn; Kheradmand‐Boroujeni, Bahman; Ellinger, Frank; Kasemann, Daniel; Leo, Karl
Abstract : An optimized vertical organic permeable‐base transistor (OPBT) competing with the best organic field‐effect transistors in performance, while employing low‐cost fabrication techniques, is presented. The OPBT stands out by its excellent power efficiency at the highest frequencies.